A Modified Design of Multilevel Inverter Using Sinusoidal Pulse Width Modulation - et. al., M.Revathi , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Multi-level Inverter technology is gaining popularity and been a momentous choice in the region of the high-power medium voltage-energy control. Producing high quality without the use of more count of switches and thus the development of such low switch Multi Level Inverter (MLI) topologies are concentrated more in this current research. These have the ability to meet the increasing demand of power rating using improved power quality through subsequent reduction in harmonic distortion. MLIs have their impression in the fields of large electric drives, traction, renewable energy conversion, electric vehicles, active power filters, HVDC and facts. The multi-level inverter generate a quasi sinusoidal voltage from various level of DC voltage. The proposed inverter is a 15-level cascaded MLI inverter and 23-level being its extension. These both are created by using the Level Shifted-Sinusoidal Pulse Width Modulation (LS-SPWM) technique. Reduction in the Total Harmonic Distortion (THD) has been the chief aim of the selected pattern. It gave a superior result in the THD. The proposed configuration overcomes the drawbacks of MLIs such as complexity, need of great number of power devices. It has less number of switches resulting in more levels of count from 15 to 23. Thus reduces the cost and gets better reliability for medium power applications. The proposed topology is simulated using MATLAB/SIMULINKR2013a and is verified.